2020
DOI: 10.1002/ppul.24884
|View full text |Cite
|
Sign up to set email alerts
|

Impact of respiratory viral polymerase chain reaction testing on de‐escalation of antibiotic therapy in children who require chronic positive pressure ventilation

Abstract: BackgroundChildren who require chronic positive pressure ventilation (CPPV) are frequently hospitalized with acute respiratory infections. Although respiratory viral testing is often performed, it is unclear how positive results impact antibiotic use. We sought to assess the impact of respiratory viral testing on antibiotic use in hospitalized children on CPPV.MethodsThis retrospective cohort study included hospitalized children on CPPV who had respiratory viral polymerase chain reaction (RVP) testing on admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[7][8][9][10][11][12] Newer molecular-based platforms enable more rapid pathogen detection with enhanced sensitivity and specificity. Although some pediatric studies using these newer platforms have reported associations with decreased antibiotic use and hospital length of stay among inpatients, 10,13 guidance regarding whether the same benefits exist for patients in an ED or urgent care setting is limited in the pediatric population. The objective of this randomized clinical trial was to determine whether knowledge of the pathogen associated with acute respiratory infection affects clinicians' decision-making regarding antibiotic prescribing and health care use in a pediatric ED setting.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Newer molecular-based platforms enable more rapid pathogen detection with enhanced sensitivity and specificity. Although some pediatric studies using these newer platforms have reported associations with decreased antibiotic use and hospital length of stay among inpatients, 10,13 guidance regarding whether the same benefits exist for patients in an ED or urgent care setting is limited in the pediatric population. The objective of this randomized clinical trial was to determine whether knowledge of the pathogen associated with acute respiratory infection affects clinicians' decision-making regarding antibiotic prescribing and health care use in a pediatric ED setting.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalization rates from common pediatric respiratory viruses have been previously described in the literature 2 . For inpatient settings, prior studies suggest that rapid identification of respiratory infections results in improved outcomes for hospitalized patients, including decreased hospitalization rates, shorter length of stay, decreased antibiotic use, and improved antiviral use 6,7 . However, less is known about the clinical impact of viral identification for children being evaluated in the ED setting, and whether knowledge of the specific respiratory pathogen can inform clinical outcomes and illness course for these children.…”
Section: Introductionmentioning
confidence: 99%
“…2 For inpatient settings, prior studies suggest that rapid identification of respiratory infections results in improved outcomes for hospitalized patients, including decreased hospitalization rates, shorter length of stay, decreased antibiotic use, and improved antiviral use. 6,7 However, less is known about the clinical impact of viral identification for children being evaluated in the ED setting, and whether knowledge of the specific respiratory pathogen can inform clinical outcomes and illness course for these children. Therefore, the objectives of this study were to explore the clinical characteristics, hospitalization risk, and symptom duration by the respiratory pathogen, of children with acute respiratory infections (ARI) evaluated in an ED setting.…”
Section: Introductionmentioning
confidence: 99%